Fungal infection in the compromised patient - Warnock, D. W; Richardson, M. D (John Wiley and Sons, 1991)
This new edition brings together in a single volume the clinical, mycological, immunological and therapeutic aspects of fungal infections occurring in the compromised patient. Chapter one outlines the mechanisms underlying the pathogenesis of fungal infection and chapter two presents the factors that predispose the compromised patient to fungal infection. These chapters serve as an introduction to the rest of the monograph, which is concerned with the diagnosis and management of particular fungal infections. Individual chapters deal in turn with each of the more frequent infections that occur in the compromised patient and an additional chapter brings together data on a number of the less common infections that have been reported. There is a new chapter which describes the manifestations of the various superficial infections in the compromised host, while a final section reviews serological methods used in diagnosis of fungal infection.
Keywords: mykózy - komplikace - následky - terapie - příručky; mikrobiologie, lékařská mikrobiologie; infekční lékařství; imunosuprese - mykózy - terapie - příručky; alergologie a imunologie